Bangladesh : Financial Accountability for Good Governance - World Bank (Washington, DC, 2013)
This document assesses the quality of financial accountability and transparency in Bangladesh, and makes recommendations for improvement. With respect to public funds, it compares the financial management standards, and practices of agencies using such funds against and international, or "best practice" standard, and also the standards, and practices of the external "oversight" agencies - nine Audit Directorates of the Comptroller and Auditor General's Office, parliamentary committees concerned with public expenditure, donor agencies, and the media. It assesses what it would take to qualify the country for programmatic, or sector lending in replacement of all individual project lending. With respect to private funds in the hands of companies, commercial banks, insurance companies, and nongovernmental organizations (NGOs), it examines the regulatory activities of the Registrar of Joint Stock Companies, the Securities and Exchange Commission, the two Stock Exchanges, Bangladesh Bank, NGO Affairs Bureau, and the accounting and auditing profession that serves both public, and private sectors.